E-INVITATION SEBAGAI PELUANG BISNIS ERA INDUSTRI 4.0 DI BALI - Wina Pertiwi Putri Wardani; Anak Agung Gde Bagus Udayana (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2021)
In the 4.0 era, everything uses technology, including the dissemination of information such as wedding invitations. It can be said that in Bali the use of e-invitation is not as popular as in Southeast Sulawesi, South Sulawesi, Aceh, West Sumatra and Central Java. This study aims to describe the potential of e-invitation in the new era, especially in Bali. Qualitative descriptive method was used in this study to explore information about the importance of using e-invitation in the pandemic era and could be a business opportunity. This paper uses high concept theory and high touch and visual elements as supporting theory in data analysis method. From the research results, it is known that e-invitation has wide-open business potential in Bali. The use of e-invitation has many advantages both from an economic and environmental point of view, it's just that few people know where the e-invitation design can be made.